Fecal Sterols in Estuarine Sediments as Markers of Sewage Contamination in the Cubatao Area, São Paulo, Brazil - Campos, Valquiria [UNESP]; Fracacio, Renata [UNESP]; Fraceto, Leonardo F. [UNESP]; Rosa, Andre H. [UNESP] (Springer, 2012)
Sterol biomarkers serve as an alternative method for detecting sewage pollution. Sterols were extracted from samples of surface sediment collected in Cubato (the Vila dos Pescadores and Vila Esperan double dagger a communities) and quantified using GC-MS after Soxhlet extraction, cleanup, and derivatization. Fecal contamination was evaluated based on the concentration of coprostanol and the ratio of the selected sterols. The most abundant sterol was cholestanol, followed by coprostanol. The concentrations of coprostanol in surface sediments ranged from a minimum of 4.21 mu g g(-1) dry sediment (Vila dos Pescadores station) to a maximum of 8.32 mu g g(-1) dry sediment (Vila Esperan double dagger a station). A coprostanol concentration of about 10 mu g g(-1) was found, indicating areas of high sewage contamination. Coprostanol levels at sewage stations were higher than in other Brazilian coastal areas, which may be attributed to the fraction of the population without sanitation services.
Keywords: Mangrove swamps; Fecal sterols; Sewage pollution; Cubatao, São Paulo